(untitled) (Journal of Asian Development Studies, 2025)
The research examines the influence of YouTube Kids on science learning motivation among elementary school students by employing a quantitative survey-based methodology. Participants were divided into two groups: an experimental group (n=20), which engaged with curated science videos on YouTube Kids, and a control group (n=20), which received traditional classroom instruction. Data were collected exclusively through a validated 29-item Likert-scale questionnaire measuring students’ interest in science topics, inquiry inclination, and interest in science-related careers. Results indicated that the experimental group displayed significantly greater improvements in motivation scores (mean pre-intervention = 3.45, post-intervention = 4.12, mean gain = 0.67) compared to the control group (mean pre-intervention = 3.50, post-intervention = 3.78, mean gain = 0.28). A repeated-measures ANOVA confirmed significant motivational growth over the intervention period (F(1,38) = 21.78, p < 0.001), highlighting the effectiveness of digital multimedia approaches. The study suggests that YouTube Kids can effectively enhance children’s motivation towards science education, provided that the content is carefully curated and monitored by educators and parents.